Resident mesenchymal vascular progenitors modulate adaptive angiogenesis and pulmonary remodeling via regulation of canonical Wnt signaling. Issue 8 (13th June 2020) - Summers, Megan E.; Richmond, Bradley W.; Menon, Swapna; Sheridan, Ryan M.; Kropski, Jonathan A.; Majka, Sarah A.; Taketo, M. Mark; Bastarache, Julie A.; West, James D.; De Langhe, Stijn; Geraghty, Patrick; Klemm, Dwight J.; et al.
Abstract: Adaptive angiogenesis is necessary for tissue repair, however, it may also be associated with the exacerbation of injury and development of chronic disease. In these studies, we demonstrate that lung mesenchymal vascular progenitor cells (MVPC) modulate adaptive angiogenesis via lineage trace, depletion of MVPC, and modulation of β‐catenin expression. Single cell sequencing confirmed MVPC as multipotential vascular progenitors, thus, genetic depletion resulted in alveolar simplification with reduced adaptive angiogenesis. Following vascular endothelial injury, Wnt activation in MVPC was sufficient to elicit an emphysema‐like phenotype characterized by increased MLI, fibrosis, and MVPC driven adaptive angiogenesis. Lastly, activation of Wnt/β‐catenin signaling skewed the profile of human and murine MVPC toward an adaptive phenotype. These data suggest that lung MVPC drive angiogenesis in response to injury and regulate the microvascular niche as well as subsequent distal lung tissue architecture via Wnt signaling.